Association between Psoriasis and Obesity - Pandey, Sumit; Jha, Smita; B.K, Shyam Kumar; B.K., Shyam Kumar; Pokharel, Kumar (Journal of Nepalgunj Medical College, 2018)
Background: Psoriasis is primarily a chronic skin disease, the course being punctuated by remissions and relapses. Research has shown that hypertension, obesity, heart failure and diabetes are significantly more common in patients with psoriasis. Obesity is associated with severe psoriasis and is reported about twice as frequently among psoriasis patients as in the general population. In recent years many reports have demonstrated an association between psoriasis and metabolic syndrome. Objectives: The aim of this study was to identify the prevalence of obesity in patients with psoriasis and compare it with that of non-psoriatic population. Material and Method: This study is a case control hospital based study conducted in the Department of Dermatology, Venereologyand Leprology of Nepalgunj Medical College Teaching Hospital, Kohalpur between May 2017 to October 2018.Total 56 cases of psoriasis and similar number of healthy age and sex matched controls were enrolled in the study after taking written consent. Detailed history and physical examination was performed with measurement of body mass index which was recorded. Statistical analysis was done using SPSS 20. Result: The results of the study which included 56 patients with psoriasis and 56 subjects without psoriasis. Among them 26 male and 30 female in study population and 25 male and 31 female in control group. The mean age was41.68±19.04 years in study population and 39.46 ±16.27 years in control group. Duration of disease ranged from 2 months to 360months and PASI score ranged from 4.4 to 28.2 with mean PASI score 11.02±5.4. BMI in cases ranged from 16.7 to 34.2 with mean24.3±4.3 and in controls it ranged from 15.5 to 29.1 with mean 21.9±3. Mean BMI was significantly higher in cases than controls. Conclusion: The result of this study supports the significantly higher prevalence of obesity in study population than control group.